Opportunities and challenges halal tourism in Indonesia in the era of human-centered technology (society 5.0) - Fikry Ramadhan Suhendar; Nurlailiyah Aidatus Sholihah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Indonesia, as a Muslim-majority country, has great potential in developing halal tourism that meets the needs and preferences of Muslim travelers. However, in its implementation, the sector faces various challenges. Along with the emergence of Society 5.0, which focuses on technology that empowers humans, the challenges and opportunities in the development of halal tourism are also increasingly complex. Society 5.0 aims to answer and address social issues that arise along with the industrial revolution 4.0, by placing humans at the center of innovation. This study aims to analyze the opportunities and challenges faced by halal tourism in the Society 5.0 era. The research method used is a qualitative method with written data collection techniques through literature studies. After the data is collected, it is then analyzed descriptively to produce research findings. The results showed that halal tourism in the Society 5.0 era has good opportunities thanks to the role of technology in improving access to information, personalization of tourist experiences, operational efficiency, and the development of innovative halal tourism products. However, major challenges are still faced related to standardization, infrastructure quality, human resource quality, global competition, and cybersecurity risks. Overcoming these challenges requires a collaborative strategy between the government and the private sector, utilization of technology for efficiency and safety, improving the quality of human resources, and more intensive promotion in both domestic and international markets. With the implementation of this strategy, Indonesia's halal tourism sector can develop optimally, strengthen the country's economy, and meet global market demand.